Three-Dimensional Structure Characterization and Inhibition Study of Exfoliative Toxin D From Staphylococcus aureus - Ullah, Anwar; Khan, Ajmal; Al-Harrasi, Ahmed; Ullah, Kifayat; Shabbir, Asghar (Frontiers in Pharmacology, 2022)
The Staphylococcus aureus (S. aureus) exfoliative toxins (ETs) are the main toxins that produce staphylococcal scalded skin syndrome (SSSS), an abscess skin disorder. The victims of the disease are usually newborns and kids, as well as grownup people. Five exfoliative toxins namely, exfoliative toxins A, B, C, D, and E have been identified in the S. aureus. Of these, the three-dimensional (3D) structure of Exfoliative toxins A, B, C & E is known, while that of exfoliative toxin D is still unknown. In this work, we have predicted the three-dimensional structure of exfoliative toxin D (ETD) using protein modeling techniques (software used for 3D comprising, MODELLER 9v19 program, SWISS-Model, and I-TESSER). The validation of the build model was done using PROCHECK (Ramchandran plot), ERRAT2 and Verify 3D programs. This represents the first structure report of ETD. The 3D structure analysis indicates that the overall structure of ETD is similar to the chymotrypsin-like serine protease fold. The structure is composed of thirteen β-strands and seven α-helices that fold into two well-defined six-strand β-barrels whose axes are roughly perpendicular to each other. The active site residues include Histidine-97, Aspartic acid-147, and Serine-221. Structural comparison with other ETs shows some differences particularly in the loop region, which also change the overall surface charge of these toxins. This may convey variable substrate specificity to these toxins. The inhibition of these toxins by natural (2S albumin and flocculating proteins from Moringa oleifera seeds) and synthetic inhibitors (Suramin) was also carried out in this study. Molecular Dynamic Simulation was performed to see the effect of inhibitor binding to the enzyme. This work will further elucidate the structure-function relationship of this enzyme. The inhibition of this enzyme will lead to a new treatment for SSSS.